PERBANDINGAN BENTUK LATIHAN TRIANGLE DAN BENTUK LATIHAN EL RONDO TERHADAP AKURASI PASSING PADA PESERTA EKSTRAKURIKULER FUTSAL SMP SITI AISYAH KADUNGORA - kosasih, Alam Hadi (JUARA : Jurnal Olahraga, 2025)
The problem in this research is a lack of understanding and mastery of basic passing techniques due to the lack of practice variations which make contact with the ball on the foot impact accuracy when passing. This research aims to determine the effect of triangle and el rondo training on passing accuracy. This type of research is experimental with a two group pretest-posttest design. The subjects studied were 15 futsal extracurricular participants at Siti Aisyah Kadungora Middle School. The test used is shortpass, which has a validity of 0.68 and a reliability of 1.20. Data analysis used a t-test with a significance of 0.05%. The results of this study show that before treatment thit = 2.74 > ttable = 3.01. After being given treatment, thit results were 10.28 > ttable 2.82. The Gain result is 0.86. It was concluded that training with a triangle shape increased by 68%. With the elrondo form of training, there was an increase of 15%, there was a difference in results between the triangle form of training and the elrondo form of training on futsal passing accuracy for Siti Aisyah Middle School futal extracurricular participants.